(untitled) (American Journal of Youth and Women Empowerment, 2022)
The positive effect of dance engagement on the psychological well-being of individuals has been consistently established based on previously conducted studies. On the other side, no evidence was found in the moderating and mediating role of motivation in the relationship between the two variables. As a solution, this study is focused on determining the moderating and mediating role of dance motivation to dance engagement and psychological well-being. This study has adopted three questionnaires, namely: Dance Motivation Questionnaire (DMQ), the Sports Engagement Scale (SPS), and Psychological Wellbeing Scale (PWS). Additionally, Partial Least-Squares Structural Equation Modelling (PLS-SEM) using SmartPLS4 was performed to analyze the data. Analysis based on factor loading, average variance extracted (AVE), Fornell-Larcker Criterion, Cross loading, and HTMT were performed to establish the reliability and validity of the questionnaires (convergent and discriminant). After surveying 117 students taking Bachelor of Performing Arts at City College of Angeles, dance engagement positively effects students’ psychological well-being, which is consistent based on previously conducted studies. On the other hand, motivation has no moderating and mediating role in the relationship between the two variables. The study highly suggests conducting a similar study to support or refute the claim of this investigation.